Drought Stress Induces Morpho-Physiological and Proteome Changes of Pandanus amaryllifolius - Amnan MAM; Aizat WM; Khaidizar FD; Tan BC (MDPI (Basel, Switzerland), 2022)
Drought is one of the significant threats to the agricultural sector. However, there is limited knowledge on plant response to drought stress and post-drought recovery. Pandanus amaryllifolius, a moderate drought-tolerant plant, is well-known for its ability to survive in low-level soil moisture conditions. Understanding the molecular regulation of drought stress signaling in this plant could help guide the rational design of crop plants to counter this environmental challenge. This study aimed to determine the morpho-physiological, biochemical, and protein changes of P. amaryllifolius in response to drought stress and during recovery. Drought significantly reduced the leaf relative water content and chlorophyll content of P. amaryllifolius. In contrast, relative electrolyte leakage, proline and malondialdehyde contents, and the activities of antioxidant enzymes in the drought-treated and recovered samples were relatively higher than the well-watered sample. The protein changes between drought-stressed, well-watered, and recovered plants were evaluated using tandem mass tags (TMT)-based quantitative proteomics. Of the 1415 differentially abundant proteins, 74 were significantly altered. The majority of proteins differing between them were related to carbon metabolism, photosynthesis, stress response, and antioxidant activity. This is the first study that reports the protein changes in response to drought stress in Pandanus. The data generated provide an insight into the drought-responsive mechanisms in P. amaryllifolius.
Keywords: Pandanus amaryllifolius; TMT-labelled LCMS/MS; antioxidant enzymes; drought stress; proteomics; stress-responsive proteins